Upper body posture in Latin American dancers: a quantitative cross-sectional study comparing different postures - Wanke, E. M.; Mörl-Kreitschmann, M.; Holzgreve, F.; Groneberg, D.; Ohlendorf, D. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background In Latin American dance sport (LD), the shoulder girdle and the torso area are particularly stressed due to the dance style specific requirements. The aim of the study was to define differences in various dance specific upper body postures in Latin American dancers and to show gender-specific differences.